Using the extensible markup language (XML) to represent the accounting and acquisition library processes of the University of the Philippines library system - Alcarez, Jason C. (2004)
Develop document-type definitions (DTDs) for Extensible Markup Language (XML) representations of the accounting and acquisition library processes of the University of the Philippines Library System in Diliman. Computers, with proper software, can process XML documents regardless of the hardware used, the operating system installed, or how the document is accessed (on the same computer system or over a network connection). The aforementioned features make XML documents cross-platform compatible. Systems analysis and design (SAD) and process modeling of the library processes in question yield the document-type definition. Test XML documents are created from documents gathered from the library system. These XML documents are tested against the formulated DTD. The XML documents and DTD are tested using two different operating systems (Microsoft Windows 2000 and FreeBSD 4.7) to verify cross-platform compatibility. Extensible stylesheet language transform (XSLT) documents are created to present the data in the XML documents in the more familiar formats seen in some of the collected documents. Utility programs are created by the researcher to aid in verifying the XML documents against the DTD, aid in translating the XML data with XSLT documents.